Epidemiology of nontuberculous mycobacteria in the Finger Lakes region of New York - Michael Croix; Ghinwa Dumyati; Alexandra Adams; Paul Levy; Emil Lesho; Dwight Hardy; Sonal Munsiff (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Clinical-epidemiologic data for all nontuberculous mycobacteria isolated in the 9 County Finger Lakes region of NY from 226 patients between 04/01/2018–03/31/2020 were retrospectively analyzed. Only 51% of patients meeting diagnostic criteria were treated, while 25% not meeting diagnostic criteria were also treated, indicating important knowledge gaps and research opportunities.